Synthesis and characterization on functionalized silica material for mercury removal from natural gas - 458406 Chuat, Giee Sik; Hanapi Mat, supervisor (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2008